2019
DOI: 10.1016/j.sjbs.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of different biosolids and their impact on various growth parameters of wheat (Triticum aestivum L.)

Abstract: Biosolids can be effectively recycled and applied as soil amendments for agricultural crops because they contain several important micro and macronutrients including nitrogen, phosphorus, potassium, manganese. In the current study, we evaluated the effectiveness of seven biosoilds on different growth parameters of wheat crop. The biosolids used were lime stabilized, composted, liquid mesophilic anaerobically digested (liquid MAD), thermally dried mesophilic anaerobically digested (thermally dried MAD), thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“… Dad et al. (2019) used seven types of biosolids and suggested that these biosolids have value as fertilizers and can easily replace synthetic fertilizer for agricultural use.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Dad et al. (2019) used seven types of biosolids and suggested that these biosolids have value as fertilizers and can easily replace synthetic fertilizer for agricultural use.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical characteristics of the biosolids used here are similar to those of biosolids reported in other studies—e.g., organic matter content between 242 and 910 g kg −1 , TKN content between 15,000 and 68,000 mg kg −1 , and P content between 1,000 and 36,000 mg kg −1 ( Vieira et al., 2005 ; Boeira and Maximiliano, 2009 ; Rigby et al., 2016 ; Kumar et al., 2017 ; Dad et al., 2019 ; Collivignarelli et al., 2019 ). Notably, thermal drying of biosolids does not affect their chemical characteristics ( Smith and Durham, 2002 ; Ramírez et al., 2008 ; Tarrasón et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations